Экономическая ментальность украинского этноса - Ефременко, Т. (Социология: теория, методы, маркетинг, 2007)
The author treats economic mentality as a constituent of Ukrainian ethnic mentality. To describe this extremely complicated phenomenon, the author applies historiographic method which allows expounding a variety of views on the Ukrainian mentality and making its complex interpretation. General characteristics of the Ukrainians' economic mentality are supplemented with the present-day appraisals based on empirical data of sociological researches.